2020
DOI: 10.1097/md.0000000000023541
|View full text |Cite
|
Sign up to set email alerts
|

Low-residue versus clear liquid diet before colonoscopy

Abstract: Great value in the early identification and treatment of adenomatous polyps or early canceration using colonoscopy has been recognized. A clear colonoscopic vision brought by good intestinal preparation will become crucial. Several studies have completed using the low-residue diet (LRD) versus a clear liquid diet (CLD) the day before colonoscopy that presenting contradictory results. Therefore, a more comprehensive and updated meta-analysis is needed to summarize the findings on the effects of LRD and CLD on i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…To our best knowledge, this is the first real‐world study on this issue. LRDs are known to have similar efficacy for bowel preparation and better tolerability than clear liquid diets 17,18,23,24 . Furthermore, Chen et al 17 performed an updated meta‐analysis of 13 controlled trials that compared 1‐day LRD and clear liquid diets, and the results strongly suggested the feasibility of a 1‐day LRD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our best knowledge, this is the first real‐world study on this issue. LRDs are known to have similar efficacy for bowel preparation and better tolerability than clear liquid diets 17,18,23,24 . Furthermore, Chen et al 17 performed an updated meta‐analysis of 13 controlled trials that compared 1‐day LRD and clear liquid diets, and the results strongly suggested the feasibility of a 1‐day LRD.…”
Section: Discussionmentioning
confidence: 99%
“…However, a consensus on the best timing and duration of the LRD has not been achieved. Although an LRD has exhibited better tolerability without impairing the bowel preparation compared with a clear liquid diet, [16][17][18] a prolonged LRD can potentially hinder the willingness of patients to receive a colonoscopy.…”
mentioning
confidence: 99%
“…On the day before the colonoscopy, two meta-analyses compared a low-residue diet to a clear liquid diet, with both arms using the same laxative. When compared to a clear liquid diet, Nguyen et al [ 33 ] discovered that a low residue diet was associated with better tolerability (OR = 1.92, 95%CI 1.36-2.70, P < 0.01) and higher willingness to repeat bowel preparation (OR = 1.86, 95%CI 1.34-2.59, P < 0.01). However, no differences in adequate bowel cleansing (OR = 1.21, 95%CI 0.64-2.28, P = 0.58) or adverse event incidence (OR = 0.88, 95%CI 0.58-1.35, P = 0.57) were found[ 33 ].…”
Section: Factors Influencing the Quality Of Bowel Preparationmentioning
confidence: 99%
“…When compared to a clear liquid diet, Nguyen et al [ 33 ] discovered that a low residue diet was associated with better tolerability (OR = 1.92, 95%CI 1.36-2.70, P < 0.01) and higher willingness to repeat bowel preparation (OR = 1.86, 95%CI 1.34-2.59, P < 0.01). However, no differences in adequate bowel cleansing (OR = 1.21, 95%CI 0.64-2.28, P = 0.58) or adverse event incidence (OR = 0.88, 95%CI 0.58-1.35, P = 0.57) were found[ 33 ]. Another meta-analysis, this time by Avalos et al [ 34 ], compared a low-residue diet or a regular diet to a clear liquid diet.…”
Section: Factors Influencing the Quality Of Bowel Preparationmentioning
confidence: 99%
“…Fourth, most patients were on clear liquids the day before colonoscopy. Considerable data indicate low residue diets for part of the day before colonoscopy lead to improvement in tolerability of the bowel preparation 21–25. Greater use of low residue diets during the study interval could have led to a change in the extent to which bowel preparation dominated the unpleasant aspects of the colonoscopy experience.…”
Section: Discussionmentioning
confidence: 99%